Mentorship of Underrepresented Physicians and Trainees in Academic Medicine: a Systematic Review - Bonifacino, Eliana (J Gen Intern Med, 2021)
BACKGROUND: Though the USA is becoming increasingly diverse, the physician workforce contains a disproportionately low number of physicians from racial and ethnic groups that are described as underrepresented in medicine (URiM). Mentorship has been proposed as one way to improve the retention and experiences of URiM physicians and trainees. The objective of this systematic review was to identify and describe mentoring programs for URiM physicians in academic medicine and to describe important themes from existing literature that can aid in the development of URiM mentorship programs. METHODS: The authors searched PubMed, PsycINFO, ERIC, and Cochrane databases, and included original publications that described a US mentorship program involving academic medical doctors at the faculty or trainee level and were created for physicians who are URiM or provided results stratified by race/ethnicity. RESULTS: Our search yielded 4,548 unique citations and 31 publications met our inclusion criteria. Frequently cited objectives of these programs were to improve research skills, to diversify representation in specific fields, and to recruit and retain URiM participants. Subjective outcomes were primarily participant satisfaction with the program and/or work climate. The dyad model of mentoring was the most common, though several novel models were also described. Program evaluations were primarily subjective and reported high satisfaction, although some reported objective outcomes including publications, retention, and promotion. All showed satisfactory outcomes for the mentorship programs. DISCUSSION: This review describes a range of successful mentoring programs for URiM physicians. Our recommendations based on our review include the importance of institutional support for diversity, tailoring programs to local needs and resources, training mentors, and utilizing URiM and non-URiM mentors. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11606-020-06478-7.